Evaluation of a Multilocus Indel DNA Region for the Detection of the Wheat Tan Spot Pathogen Pyrenophora tritici-repentis - See, Pao Theen; Moffat, Caroline; Morina, J.; Oliver, Richard (American Phytopathological Society, 2016)
Tan spot or yellow (leaf) spot disease of wheat (Triticum spp.) is caused by Pyrenophora tritici-repentis, a necrotrophic fungal pathogen that is wide-spread throughout the main wheat-growing regions in the world. This disease is currently the single most economically important crop disease in Australia. IN this study, a real-time quantitative polymerase chain reaction (qPCR) assay was developed as a diagnostic tool to detect the pathogen on wheat foliar tissue. A multicopy locus (PtrMulti) present in the P. tritici-repentis genome was assessed for its suitability as a qPCR probe. The primer pair PtrMulti_F/R that targets the region was evaluated with respect to species specificity and sensitivity. A PtrMulti SYBR qPCR assay was developed and proved to be suitable for the identification and relative quantification of P. tritici-repentis with a detection limi of DNA levels at <0.1 pg. Variation of the PtrMulti copy number between the geographical representatives of P. tritici-repentis strains examined was minimal, with the range of 63 to 85 copies per genome. For naturally infected wheat field samples, the incidence of P. tritici-repentis DNA on leaves quantified by qPCR varied up to 1,000-fold difference in the concentration, with a higher incidence of DNA on the younger leaves in the absence of visible tan spot lesions. These results demonstrate the potential of PtrMulti probe to be used for early detection and rapid screening of tan spot disease on wheat plants.